THE EFFECT OF QUANTUM TEACHING MODEL BASED LITERACY TOWARD STUDENT CRITICAL THINKING SKILL - Reflina Reflina; Suendri Suendri; Nurlaili Nurlaili; Rizqy Khairiah Fadhila (JURNAL TARBIYAH, 2020)
This study is aimed to see the effect of quantum teaching model based on literacy toward student’s ability in critical thinking focused on flat side building in SMP Plus Darul Ilmi Murni. The method of this study is quantitative research by using quasi experimental research. The total number of sample is 19 students for each classes, they are experimental and control class. Based on the data and analysis, it shows that there is significant differences between T-Count and T-table. The analysis of the data resulted that T-test is 4,226 and T-Table is 5 % (1,689). From the percentage, it can be seen that , it is , thus H0 is rejected and  Ha is accepted. Therefore, the hypothesis can conclude that there is a significant effect of quantum teaching based literacy toward student’s ability in critical thinking focused on flat side building in SMP Plus Darul Ilmi Murni